PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DENGAN MEDIA PUZZLE UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR DI MTS.SIROJUL ULUM MAYANG JEMBER - Hartono, Rudi; -, Suratno; Khusnah, Laila (Pendidikan Biologi,Universitas Islam Jember, 2013)
This research is taken because the result of students test in 2010/2011 was 69,4 in avarage (the minimum target was 75) with classical completeness 60% of 85%. There fore it is needed to do a research to improve the will and result of student in their study. This kind of research is called class action research by using 2 cycle models in quantitatif methode. Based on the result of the research, it is found the result of students will to study in the cycle I found 3,7 in average with positive criteria and in cycle II found 4,3 in avarage with a very positive criteria. While the result of student study in the cycle I got 73,60 in avarage result with 88% classical completeness and in cycle II got 87,48 in avarage result with 96% classical completeness. From the cycle I and II data above, it can be conclueded that the three results are getting improved effisiently, they are the students will to study improve 13,95%, and the result of students study 15,87%, and the completeness of student study result 8,3%. By those result it is shown that the student are very interested to study with cooperative learning model type STAD by using puzzle media. Keywords : Learning of sains, type STAD with Puzzle Media